The post-Cold War era, the Persian Gulf War, and the peace and justice movement in the 1990s - Novotny, Patrick (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writer discusses the redefinition of the peace and justice movement in the post-cold war era of the 1990s. He argues that the peace and justice movement in the 1990s has incorporated larger struggles against the consequences of globalization abroad and privatized downsized government at home. He traces the role of the peace and justice movement in the Persian Gulf. He highlights the work of individual groups in this movement, such as the Urban Habitat Program and the Southern Organizing Committee for Economic and Social Justice. He identifies the peace and justice movement's struggle in the post-cold war period as being a struggle for the reorientation of the post-cold War economy from being environmentally destructive to being more sustainable. He proposes that the movement requires a broader political strategy to transform policy at the national and international level and must articulate a more inclusive definition of security.